Gaya Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pada SMKN Taman Fajar Aceh Timur - Jamil, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to examine the leadership style of school principals in improving teacher performance at SMKN Taman Fajar East Aceh. This study uses a qualitative research method with a case study approach. Data collection was carried out through observation and interviews with 31 teachers at SMKN Taman Fajar East Aceh. The results of the study show that there is a significant positive relationship between the principal's leadership style and teacher performance. The transformational leadership style which includes inspiring, motivating and empowering teachers, as well as the transactional leadership style which includes giving gifts and punishments has a strong effect on teacher performance at SMKN Taman Fajar East Aceh. Good communication is a key factor in building a harmonious and mutually supportive working relationship between the principal and teachers at SMKN Taman Fajar.